Analysis of Using Support Vector Regression (SVR) Algorithm to Predict The Occurrence of Sea Tides in Tanjung Medang, Riau by Saas Storage in Cloud Computing - Dinda Faatihah Ramadhani Putri; Ita Arianti; Julydio Windu Nugroho; Silviya (Jurnal Mandiri IT, 2022)
Tides in the waters of Tanjung Medang, Riau, have an important role of lives in communities around the coast, one of them is to help a fishermen when they want to go to sea. Cloud computing is an online based data storage that can make various human activities easier. The method that we used for this research is Support Vector Regression (SVR) with Cost (C) and Gamma parameters. The purpose of this research is to obtain the data accuracy and determine the RMSE value of the model in data processing process. The data will be stored through one of the cloud computing technologies, namely Software As A Service (SaaS) storage. Based on the research result, the Support Vector Regression (SVR) model was good enough to be used in processing tidal prediction data used Gamma parameter with a gain value of 100 and RMSE value of 0.451896.